ЕКОЛОГІЧНА КОМПОНЕНТА СТАЛОГО РОЗВИТКУ: ВІД ТЕОРІЇ ДО ІМПЛЕМЕНТАЦІЇ (Світ фінансів, 2018)
Длугопольський О. В. Екологічна компонента сталого розвитку: від тєорії до імплементації. Окреслено проблему екологізації економічного прогресу в контексті стратегії сталого розвитку, проаналізовано ключові теорії, пов’язані зі змінами клімату та впливами на показники добробуту, досліджено міжнародні ініціативи екологізації (Кіотський протокол, Копенгагенська і Паризькі угоди), сформульовано висновки стосовно майбутнього розвитку країн світу в контексті екологізації. Виокремлено ключові тенденції еколого-економічного розвитку.  Длугопольский А. В. Экологическая компонента сбалансированного развития: от теорий к имплементации. Определена проблема экологизации экономического прогресса в контексте стратегии сбалансированного развития. Проанализированы ключевые теории, связанные с изменениями климата и влиянием на показатели благосостояния, исследованы международные инициативы экологизации (Киотский протокол, Копенгагенское и Парижское соглашения), сформулированы выводы относительно будущего развития стран мира в контексте экологизации. Выделены ключевые тенденции эколого-экономического развития.  Dluhopolskyi О. Ecological component ofsustainable development: from theoryes to implementation. Introduction. The article deals with the problem of ecologization of economic progress in a context of sustainable development. Different approaches of Kuznetz ecological curve focused on political, income and inequality factors are discussed. The key concepts of climate changings and impact of welfare indicators are analyzed. The key international initiatives of ecologization are discussed (Kyoto protocol, Copenhagen and Paris agreements).Purpose. The purpose of the paper is generalization of key approaches of economic development ecologization and identification the conducive trends of international climate initiatives.Results. The appearance of the welfare paradox in the process of economic development and ecologization interaction is substantiated. Main features of ecological racism as inequality in external environmental conditions which leads to deterioration of the health of people belonging to different races are considered. The results of the survey in several communities of Ternopil, Kyiv, Sumy, Donetsk, Zaporizhia, Poltava regions showed that 88% of Ukrainians believe that there is a threat of a global environmental crisis. Ukrainians consider that the most significant factors of the ecological crisis are transport (41% of respondents), industry (32%), financial and industrial groups (14%), increase in population (5%), increase of natural anomalies (5%), thermal stations (3%). 47% of respondents are ready to invest in reducing greenhouse gas emissions.Conclusions. The formation of new model of national economies ecologization in the context of welfare provision is actual today because there are lack of effective operational concepts and there are new challenges: climate change, population aging, environmental and public finance crises, new requirements for the quality and quantity of public goods, etc.